Analyzing the impoliteness of netizens in commenting on the Deddy Corbuzier Podcast - Mey Trisnawati Hulu; Elwin Piarawan Zebua (Journal of Language Education (JoLE), 2024)
The aims of this research are to find out the kind of impoliteness strategies that netizens comment on the Deddy Corbuzier Podcast and to find the most dominant type of impoliteness strategies that netizens use in comments on Deddy Corbuzier's podcast. Since the data for this study were gathered in the form of word sentences, a descriptive qualitative approach was used to conduct it. The data used in this study were gathered from a podcast by Deddy Corbuzier. based on the findings, it can be concluded that in the comments column of Deddy Corbuzier's podcast account, Four types of impoliteness strategies are Bald on Record Impoliteness (1,16%), and Positive Impoliteness (67,44%). It consists of 43,02% where the readers use taboo words, 15,11% calling out other people’s names, and 9,30% case of be unconcerned, disinterested, and unsympathetic. Negative Impoliteness (29,06%), it consists of 12,79% the action condescending, 13,95% scorning or ridiculing the other and 2,32% of fearing the other. And Sarcasm/Mock Politeness (2,32%) and the total of comments is 85 comments. based on the comments that have been analyzed, the researcher concluded that netizens mostly use positive impoliteness, It was found in 58 cases (67,44%) out of 85 comments. It consists of 38 cases where the readers use taboo words, 13 call out the other people’s names and 8 case of be unconcerned, disinterested, and unsympathetic. The majority of netizens use the where the readers use taboo words, it found in 38 cases. Positive Impoliteness is mostly used in the comment column of the Deddy Corbuzier podcast account.